Impact of single-room contact precautions on hospital-acquisition and transmission of multidrug-resistant Escherichia coli: a prospective multicentre cohort study in haematological and oncological wards. (August 2019) - Biehl, L.M.; Higgins, P.; Wille, T.; Peter, K.; Hamprecht, A.; Peter, S.; Dörfel, D.; Vogel, W.; Häfner, H.; Lemmen, S.; Panse, J.; Rohde, H.; et al.
Abstract: Objectives: Colonization and infection with third-generation cephalosporin-resistant Escherichia coli (3GCR-EC) are frequent in haematological and oncological patients. In this high-risk setting, German guidelines recommend single-room contact precautions (SCP) for patients with 3GCR-EC that are non-susceptible to fluoroquinolones (F3GCR-EC). However, this recommendation is controversial, as evidence is limited. Methods: We performed a prospective, multicentre cohort study at four haematology and oncology departments assessing the impact of SCP on hospital-acquired colonization or bloodstream infection (BSI) with F3GCR-EC. Two sites performed SCP for F3GCR-EC patients including single rooms, gloves and gowns (SCP sites), and two did not (NCP sites). Active screening for 3GCR-EC was performed and isolates were characterized with molecular typing methods including whole genome sequencing and core genome multiple locus sequence typing to assess patient-to-patient transmission. Potential confounders were assessed by competing-risk regression analysis. Results: Within 12 months, 1386 patients at NCP sites and 1582 patients at SCP sites were included. Hospital-acquisition of F3GCR-EC was observed in 22/1386 (1.59%) and 16/1582 (1.01%) patients, respectively (p 0.191). There were 3/1386 (0.22%) patients with BSI caused by F3GCR-EC at NCP sites and 4/1582 (0.25%) at SCP sites (p 1.000). Patient-to-patient transmission occurred in three cases at NCP and SCP sites each (p 1.000). The number of patients needed to screen in order to prevent one patient-to-patient transmission of F3GCR-EC was determined to be 3729. Conclusions: Use of SCP had no significant impact on hospital-acquisition or patient-to-patient transmission of F3GCR-EC in this high-risk setting.